A New Metric of the Biological Carbon Pump: Number of Pump Passages and Its Control on Atmospheric pCO2. Issue 6 (8th June 2021) - Holzer, Mark; Kwon, Eun Young; Pasquier, Benoit
Abstract: We develop novel locally defined diagnostics for the efficiency of the ocean's biological pump by tracing carbon throughout its lifetime in the ocean from gas injection to outgassing and counting the number of passages through the soft‐tissue and carbonate pumps. These diagnostics reveal that the biological pump's key controls on atmospheric pCO2 are the mean number of lifetime pump passages per dissolved inorganic carbon (DIC) molecule at the surface and the mean aphotic sequestration time of regenerated DIC. We apply our diagnostics to an observationally constrained carbon‐cycle model that features spatially varying stoichiometric ratios and is embedded in a data‐assimilated global ocean circulation. We find that for the present‐day ocean an average of 44 ± 4% of DIC in a given water parcel makes at least one lifetime passage through the soft tissue pump, and about 4% makes at least one passage through the carbonate pump. The global mean number of lifetime pump passages per molecule, including the fraction with zero passages, is N ¯ soft = 0.65 ± 0.08 and N ¯ carb ∼ 0.04 for the soft‐tissue and carbonate pumps. Using idealized perturbations to sweep out a sequence of states ranging from zero biological activity ( p C O 2 atm = 493 ± 1 ppmv) to complete surface nutrient depletion ( p C O 2 atm = 207 ± 1 ppmv), we find that fractional changes in p C O 2 atm are dominated by fractional changes in the number of soft‐tissue pump passages. At complete surface nutrient depletion, the mean fraction of DIC that has at least one lifetime passage through the soft‐tissue pump increases to 69 ± 5% with N ¯ soft = 1.6 ± 0.3 . Plain Language Summary: Tiny plants floating near the ocean surface use sunlight to convert nutrients and dissolved CO2 into organic matter. A fraction of this organic matter sinks, transferring carbon from the surface to the deep ocean, a process known as the biological pump. The biological pump reduces atmospheric CO2 and is thus important for moderating climate. The organic matter is oxidized by microbes, which regenerates inorganic carbon that can then pass through the biological pump again or return to the atmosphere. Here, we calculate, for the first time, the number of passages through the biological pump that a typical carbon molecule makes during its lifetime in the ocean. This carbon‐based measure of pump efficiency is useful for quantifying the biological pump's control on atmospheric CO2 . We find that in the current state of the ocean 44 ± 4% of the dissolved inorganic carbon makes at least one lifetime passage through the biological pump, with a mean number of 0.65 ± 0.08 passages per molecule. In numerical experiments that stimulate the biological pump to utilize all available nutrients, the fraction with at least one passage increases to 69 ± 5% with 1.6 ± 0.3 passages per molecule, which draws down atmospheric CO2 by about 70 ppmv. Key Points: The mean number of passages through the biological pump per carbon molecule is a natural metric of pump efficiency Globally averaged 44 ± 4% of the dissolved carbon in a given water parcel is biologically pumped with 0.65 ± 0.08 lifetime passages per molecule Changes in atmospheric CO2 are related to changes in the mean number of pump passages and the mean injection‐tagged sequestration time